2018
DOI: 10.1093/annonc/mdx771
|View full text |Cite
|
Sign up to set email alerts
|

A prospective phase II study of combined androgen blockade in patients with androgen receptor-positive metastatic or locally advanced unresectable salivary gland carcinoma

Abstract: BackgroundThere is no standard first-line chemotherapy for recurrent/metastatic (RM) or unresectable locally advanced (LA) salivary gland carcinoma (SGC).Patients and methodsWe conducted a single institution, open-label, single arm, phase II trial of combined androgen blockade (CAB) for androgen receptor (AR)-positive SGC. Leuprorelin acetate was administered subcutaneously at a dose of 3.75 mg every 4 weeks. Bicalutamide was administered orally at a daily dose of 80 mg. Patients were treated until progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
144
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(164 citation statements)
references
References 25 publications
0
144
1
5
Order By: Relevance
“…This may cause ADT resistance by activating other tumor‐driving pathways, such as the PI3K‐AKT pathway, in the presence of an active AR pathway. It is therefore interesting to note that a positive HER2 status did not affect clinical benefit from ADT in AR and HER2 positive SDC patients, which is in line with data from other research groups . Therefore, ADT seems to be a good treatment option in these patients, but the presence of other targetable genetic markers stresses the importance of prediction of clinical benefit in order to select the most suitable therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may cause ADT resistance by activating other tumor‐driving pathways, such as the PI3K‐AKT pathway, in the presence of an active AR pathway. It is therefore interesting to note that a positive HER2 status did not affect clinical benefit from ADT in AR and HER2 positive SDC patients, which is in line with data from other research groups . Therefore, ADT seems to be a good treatment option in these patients, but the presence of other targetable genetic markers stresses the importance of prediction of clinical benefit in order to select the most suitable therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In retrospective studies, ADT has shown response rates of 17.6–50.0% and an OS of 17 months compared to 5 months in a best supportive care cohort . A recent prospective phase 2 trial in Japan showed a response rate of 41.7%, median progression‐free survival (PFS) of 8.8 months and median OS of 30.5 months . Because of the efficacy of ADT in R/M SDC patients, we evaluated ADT as adjuvant treatment in 22 patients with locally advanced (LA) AR‐positive SDC.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast to mammary ductal carcinoma, most SDCs express androgen receptor (AR) and are negative for oestrogen receptor (ER) and progesterone receptor; this hormone receptor profile suggests that SDC is more akin to prostate cancer. The role of AR in the progression of SDC has been investigated and androgen blockade therapy, which is used in the treatment of prostate cancer, has recently become the treatment of choice for SDC . It has been reported to show equivalent efficacy to conventional chemotherapy; however, the potential resistance mechanisms in SDC patients who receive androgen blockade therapy remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Androgen deprivation therapy with leuprorelin and bicalutamide in 32 patients with AR positive salivary gland cancer has response rates of 42% . A complementary study (NCT02749903) is evaluating enzalutamide alone in 45 AR positive patients with overall response rate as the primary outcome measure.…”
Section: Resultsmentioning
confidence: 99%
“…Recent progress in the molecular sub‐classification of cancers and selection of treatment based upon molecular aberrations has shown promise. In androgen receptor (AR) positive salivary gland cancer, 42% response rates with androgen deprivation therapy (leuprorelin and bicalutamide) were seen . The most dramatic gains have been reported in NTRK3 rearranged mammary analogue secretory carcinoma, with 75% response rates in a non‐randomised trial of pan‐Trk inhibition with larotrectinib in patients harbouring this gene rearrangement irrespective of primary tumour site .…”
Section: Introductionmentioning
confidence: 99%